The possibilities of diagnostic radiology for the primary identification of spleen abscesses - M. V. Grechikhina; N. A. Gorbunov; S. V. Andreeva; A. P. Dergilev (Исследования и практика в медицине)
The issue on the differential diagnosis of formations of purulent-inflammatory etiology and the choice of treatment method taking into account the visual picture does not lose its relevance. Ultrasound (US) is not less crucial than computed tomography (CT) for the primary diagnosis of spleen abscesses. This article presents clinical observations of patients with suspected spleen abscesses admitted to the emergency room of the Novosibirsk City Clinical Hospital No. 1 with emergency indications for 2017–2022. All patients underwent ultrasound with Philips Affiniti 70G, Mindray M9, and General Electric Logiq P6 devices. While performing ultrasound in In-mode, attention was paid to the main signs: localization (in the parenchyma, subcapsular), quantity, contours (wall thickness), the nature of the abscess contents, dimensions (volume calculated according to the formula for irregularly shaped formations, A × B × C × 0.52), the presence or absence of effusion in pockets the spleen. The formations were classified by volume into small (up to 50 ml), medium (50–100 ml) and large (more than 100 ml). The main ultrasound signs in the seroscale mode have been determined. The presented clinical observations illustrate the possibilities of ultrasound for deciding on the method of treatment: for primary diagnosis (including emergency), it was possible to determine the presence of formations of purulent- inflammatory etiology, to determine the localization, the main signs in which minimally invasive treatment was effective (formed abscess of "medium" volume). Surgical abdominal treatment was preferable in the presence of multiple abscesses (without a formed capsule) of small size.